Reformulation of Education Supervision in the Free Learning Policy - Syahrial Labaso’; Bayu Saputra Dullah; Ratna Hestiana (Sustainable, 2023)
The implementation of the independent learning curriculum requires an educational design that is flexible for the needs of the development of this innate potential so that educational supervision services allow for substantial shifts and changes in terms of work procedures and standardization of educational supervision services. This research uses a library research approach by collecting literature materials that are considered relevant to the theme of this research, then analyzing them and then formulating them into a conceptual paradigm as findings in this study. The findings in this study explain that the independent learning curriculum is an effort to create a learning space that is in accordance with the child's growth and development potential in order to achieve the maximum self-actualization process. This presents a new challenge for educational supervision services to be able to be adaptive and continue to open themselves to all possibilities that are considered feasible and can contribute to the achievement of maximum self-development goals so that educational supervision services are no longer limited to explaining the technical implementation of supervision operations, but must also be able to position themselves on the substitution of values contained in the learning process directed at achieving the process of maximum self-actualization. This research succeeded in building a new paradigm of mainstreaming inclusive educational supervision and a new view of the concept of educational supervision for the future.